Effects of Dextran-70 and Albumin on Coagulation in Experimental Hemorrhage in the Guinea Pig. Issue 3 (September 2018) - Schött, Ulf; Kander, Thomas; Bentzer, Peter
ABSTRACT: Background: Dextran-70 is a more potent plasma volume expander than albumin but use has been hampered because of its antithrombotic properties. However, also albumin has antithrombotic properties and little is known about relative effects of these two colloids on coagulation in vivo when controlling for differences in efficacy as plasma volume expanders. Aim: Compare effects of dextran-70 and albumin on coagulation at a dose resulting in equal plasma volume expansion. Methods: Guinea pigs were subjected to a 25 mL/kg hemorrhage during 20 min and randomized to resuscitation with either 6% dextran-70 at a dose of 15 mL/kg or 5% albumin at a dose of 25 mL/kg (n = 14 in each group) during 30 min starting 1 h of shock. Blood samples were collected at the completion of resuscitation and at 4 h. Plasma volume was measured using 125 I-albumin and the effect on coagulation was evaluated using whole blood thrombelastography (TEG), measurement of plasma fibrinogen and von Willebrand factor (vWF) concentrations and vWF glycoprotein 1b (GP1b) A activity. Results: Plasma volumes after resuscitation were similar in the groups at both time points. Dextran-70 resulted in a transient prolongation of TEG clot amplification time (K) at the completion of resuscitation compared with albumin. TEG clot initiation (R) and strength (MA) did not differ between the treatments at any of the time points. Albumin reduced vWF concentrations to a larger extent than dextran at both time points, whereas no difference in vWF GP1bA activity or in plasma fibrinogen and could be detected. Conclusion: In equipotent doses with regard to plasma volume expansion, dextran-70 transiently prolongs clot amplification time more than albumin whereas dextran-70 reduces plasma vWF concentrations less than albumin.